###### Advertisements

###### Advertisements

**State whether the following statement is True or False: **

A homogeneous differential equation is solved by substituting y = vx and integrating it

#### Options

True

False

###### Advertisements

#### Solution

**True**

#### APPEARS IN

#### RELATED QUESTIONS

Solve the differential equation (x^{2} + y^{2})dx- 2xydy = 0

Solve the differential equation :

`y+x dy/dx=x−y dy/dx`

Show that the given differential equation is homogeneous and solve each of them

(x^{2} + xy) dy = (x^{2} + y^{2}) dx

Show that the given differential equation is homogeneous and solve each of them

`y' = (x + y)/x`

Show that the given differential equation is homogeneous and solve each of them

`xdy - ydx = sqrt(x^2 + y^2) dx`

Show that the given differential equation is homogeneous and solve each of them

`{xcos(y/x) + ysin(y/x)}ydx = {ysin (y/x) - xcos(y/x)}xdy`

Show that the given differential equation is homogeneous and solve

`(1+e^(x/y))dx + e^(x/y) (1 - x/y)dy = 0`

For the differential equations find the particular solution satisfying the given condition:

(x + y) dy + (x – y) dx = 0; y = 1 when x = 1

For the differential equations find the particular solution satisfying the given condition:

`[xsin^2(y/x - y)] dx + xdy = 0; y = pi/4 when x = 1`

For the differential equations find the particular solution satisfying the given condition:

`dy/dx - y/x + cosec (y/x) = 0; y = 0 when x = 1`

(x^{2} + 3xy + y^{2}) dx − x^{2} dy = 0

(2x^{2} y + y^{3}) dx + (xy^{2} − 3x^{3}) dy = 0

Solve the following initial value problem:

\[x e^{y/x} - y + x\frac{dy}{dx} = 0, y\left( e \right) = 0\]

Solve the following initial value problem:

\[\frac{dy}{dx} - \frac{y}{x} + cosec\frac{y}{x} = 0, y\left( 1 \right) = 0\]

Solve the following initial value problem:

\[\frac{dy}{dx} = \frac{y\left( x + 2y \right)}{x\left( 2x + y \right)}, y\left( 1 \right) = 2\]

Solve the following initial value problem:

x (x^{2} + 3y^{2}) dx + y (y^{2} + 3x^{2}) dy = 0, y (1) = 1

Solve the following initial value problem:

\[\left\{ x \sin^2 \left( \frac{y}{x} \right) - y \right\}dx + x dy = 0, y\left( 1 \right) = \frac{\pi}{4}\]

Solve the following initial value problem:

\[x\frac{dy}{dx} - y + x \sin\left( \frac{y}{x} \right) = 0, y\left( 2 \right) = x\]

Find the particular solution of the differential equation x cos\[\left( \frac{y}{x} \right)\frac{dy}{dx} = y \cos\left( \frac{y}{x} \right) + x\], given that when x = 1, \[y = \frac{\pi}{4}\]

Find the particular solution of the differential equation \[\left( x - y \right)\frac{dy}{dx} = x + 2y\], given that when x = 1, y = 0.

A homogeneous differential equation of the form \[\frac{dx}{dy} = h\left( \frac{x}{y} \right)\] can be solved by making the substitution

Which of the following is a homogeneous differential equation?

Solve the differential equation: ` (dy)/(dx) = (x + y )/ (x - y )`

Solve the differential equation: x dy - y dx = `sqrt(x^2 + y^2)dx,` given that y = 0 when x = 1.

**Solve the following differential equation:**

`"x" sin ("y"/"x") "dy" = ["y" sin ("y"/"x") - "x"] "dx"`

**Solve the following differential equation:**

`(1 + 2"e"^("x"/"y")) + 2"e"^("x"/"y")(1 - "x"/"y") "dy"/"dx" = 0`

**Solve the following differential equation:**

y^{2} dx + (xy + x^{2})dy = 0

**Solve the following differential equation:**

`"dy"/"dx" + ("x" - "2y")/("2x" - "y") = 0`

**Solve the following differential equation:**

`"x" "dy"/"dx" - "y" + "x sin"("y"/"x") = 0`

**Solve the following differential equation:**

`(1 + "e"^("x"/"y"))"dx" + "e"^("x"/"y")(1 - "x"/"y")"dy" = 0`

**Solve the following differential equation:**

`"y"^2 - "x"^2 "dy"/"dx" = "xy""dy"/"dx"`

**Solve the following differential equation:**

`"xy" "dy"/"dx" = "x"^2 + "2y"^2, "y"(1) = 0`

**Solve the following differential equation:**

x dx + 2y dx = 0, when x = 2, y = 1

**Solve the following differential equation:**

`"x"^2 "dy"/"dx" = "x"^2 + "xy" + "y"^2`

**Solve the following differential equation:**

(9x + 5y) dy + (15x + 11y)dx = 0

**Solve the following differential equation:**

(x^{2} + 3xy + y2)dx - x^{2} dy = 0

**Solve the following differential equation:**

(x^{2} – y^{2})dx + 2xy dy = 0

F(x, y) = `(x^2 + y^2)/(x - y)` is a homogeneous function of degree 1.

Solcve: `x ("d"y)/("d"x) = y(log y – log x + 1)`

The solution of the differential equation `(1 + e^(x/y)) dx + e^(x/y) (1 + x/y) dy` = 0 is

A homogeneous differential equation of the `(dx)/(dy) = h(x/y)` can be solved by making the substitution.

Let the solution curve of the differential equation `x (dy)/(dx) - y = sqrt(y^2 + 16x^2)`, y(1) = 3 be y = y(x). Then y(2) is equal to ______.

If a curve y = f(x), passing through the point (1, 2), is the solution of the differential equation, 2x^{2}dy = (2xy + y^{2})dx, then `f(1/2)` is equal to ______.

The differential equation y' = `y/(x + sqrt(xy))` has general solution given by:

(where C is a constant of integration)

**Read the following passage:**

An equation involving derivatives of the dependent variable with respect to the independent variables is called a differential equation. A differential equation of the form `dy/dx` = F(x, y) is said to be homogeneous if F(x, y) is a homogeneous function of degree zero, whereas a function F(x, y) is a homogeneous function of degree n if F(λx, λy) = λ To solve a homogeneous differential equation of the type `dy/dx` = F(x, y) = `g(y/x)`, we make the substitution y = vx and then separate the variables. |

**Based on the above, answer the following questions:**

- Show that (x
^{2}– y^{2}) dx + 2xy dy = 0 is a differential equation of the type `dy/dx = g(y/x)`. (2) - Solve the above equation to find its general solution. (2)